Editor’s Note - Morente Molinera, Juan Antonio (International Journal of Interactive Multimedia and Artificial Intelligence, 2025)
The International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI) publishes articles discussing the latest current topics in the research literature. The emergence of ChatGPT and other similar models based on deep learning are dramatically changing the way people understand and use artificial intelligence. Despite the significant advances made in these types of techniques, which have been enormous in recent years, new learning methods are still needed. Specifically, we require methods that allow us to handle data correctly in specific environments, as well as provide learning methods with the necessary explainability that allows us to understand how they are reasoning. The latter is essential for creating ethical learning methods that do not make unfair decisions based on biased information. It is also important to identify data that have, in some way, reflected the reprehensible attitudes and reasoning that we as fallible human beings sometimes have. In short, artificial intelligence should reflect, if possible, the best of us rather than the worst. With this goal in mind, it is common to see in this issue of the journal an abundance of articles proposing new learning methods, many of which are based on Deep Learning and Data Mining. There are also articles on large language models, which are extremely important in the current artificial intelligence landscape. Of course, there are also articles on optimization methods and quantum computers, which are also of great importance in the field of artificial intelligence. Although generative artificial intelligence models are perhaps the ones that have people most intrigued, this is not the only current application of artificial intelligence. We are seeing how renewable energies, in particular those that come from the sun and wind, are playing an increasingly important role in global energy generation. As seen in recent events, such as the general blackout in Spain, the electricity system needs new methods that allow adequate regulation to prevent all kinds of possible failures. In this issue, two articles present new applications of artificial intelligence methods to renewable energy generation systems. Also noteworthy within this issue is the application of artificial intelligence in the field of teaching, where the aim is to provide a better learning experience for students and teachers.